Library Awareness among Non-users of Public Libraries: A Study with Reference to the Hilly Areas of Darjeeling District, West Bengal - Karkee, Prabin; Majumder, Krishnapada (Journal of Information and Knowledge, 2014)
This paper is an attempt to assess the library awareness among the non-users of Government and Government sponsored Public libraries in the hilly areas of Darjeeling district of West Bengal with respect to their personal characteristics, library membership of their family members, reasons of not becoming the library members, their familiarity with nearest public library, preference of reading materials in the library, willingness and approach to become member of library, awareness of free reading facility in the library, sources of their information needs, difficulties in obtaining their information and their opinion about the library providing these information. Hence a survey of 61 non-users of public libraries across the hilly areas was conducted through a structured questionnaire. Finally it is concluded that there is need for improvement in the public library services so that the non-users may get attracted to visit the library.